Kontribusi Pondok Pesantren Az-Zuhroh Besilam Dalam Menghadirkan Mubaligh Di Kabupaten Langkat - Muhizar Muchtar (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
This research uses qualitative naturalistic approach in collecting data by using observation instruments, questionnaires and interviews to the samples. The location of the research was conducted at Az-Zuhroh Besilam boarding school addressed in Besilam Village, Padang Tualang District, Langkat Regency. Implementation of this research conducted in 2017 in November until December 2017. In this research, the characteristics of this research subject is the head of the boarding school, the board of teachers, and the students of boarding school Az-Zuhroh. The results of this study are as follows: 1) The guidance system in Pondok Pesantren Az-Zuhrah Besilam Babussalam related in the development of talents and interests of students made in the form of extracurricular activities such as da'wah cadres, 2) The role and contribution given by Pondok Pesantren Az-Zuhroh Besilam Babussalam in giving birth to reliable young mubaligh by supporting various programs so that students can develop their da'wah potential, 3) Islamic education institution developed through boarding school Az-Zuhrah Besilam Babussalam is the development of mission of da'wah and education to society especially need continuously continue to be developed internally while still increasing the supporting facilities, teaching staff, and pesantren activities more innovative in the learning process.